Research on Locomotive Speed Sensor Fault Diagnosis Method Based on Neural Network - 周桂法; 王坚 (机车电传动)
For fault diagnosis of locomotive speed sensor, a predictor method based on RBF neural network is established, and diagnostic decision method is also proposed. The RBF neural network predictor and three kinds of fault mode of locomotive speed sensor are simulated by MATLAB. The simulation results indicate that this method can diagnose faults of the speed sensor online exactly, and provides a new idea for locomotive speed sensor fault diagnosis.